Petrogenesis of the A-type, mesoproterozoic intra-caldera rheomorphic Kathleen Ignimbrite and Comagmatic Rowland suite intrusions, West Musgrave Province, Central Australia: Products of extreme fractional crystallization in a failed rift setting - Medlin, C.; Jowitt, S.; Cas, R.; Smithies, R.; Kirkland, Chris; Maas, R.; Raveggi, M.; Howard, H.; Wingate, M. (Oxford University Press, 2014)
The Pussy Cat Group rhyolites of the Mesoproterozoic west Musgrave Province of central Australia, a constituent part of the Bentley Supergroup, were deposited during the c. 1085–1040 Ma Ngaanyatjarra Rift and Giles events, and are related to the Warakurna Large Igneous Province. This study focuses on the two silicic components of the Pussy Cat Group, the Kathleen Ignimbrite and the Rowland Suite. These silicic rocks are A-type, metaluminous (to slightly peraluminous) rhyolites and are enriched in the rare earth elements (REE) relative to average crustal abundances. The rhyolitic Kathleen Ignimbrite records an explosive caldera fill-sequence and contains, amongst others, a thick (≤500 m), initially subaqueously emplaced, rheomorphic, intra-caldera ignimbrite unit, whereas the Rowland Suite consists of a number of mineralogically and geochemically related porphyritic rhyolites that intrude throughout the Pussy Cat Group. Whole-rock geochemistry, Rb–Sr, Sm–Nd and in situ zircon Lu–Hf isotope data are indicative of a dominantly mantle-derived source for the magmas that formed the Pussy Cat Group rhyolites. Secondary ion mass spectrometry U–Pb dating of these units yields ages of 1062 ± 8, 1071 ± 5, 1076 ± 5, and 1078 ± 5 Ma. The magmas that formed these units were formed by extreme fractional crystallization of a mantle-derived basaltic magma, with minimal crustal contamination, during a failed intra-plate extensional rifting event.This final phase of fractionation generated the most evolved silicic rock suite identified to date within the entire west Musgrave Province. The new petrographic, geochronological, geochemical, and isotopic data presented within this study indicate that these two units are coeval and comagmatic, suggesting a common source for the Kathleen Ignimbrite and the entire Rowland Suite. In addition, these data suggest that the crystal-rich, porphyritic rhyolite intrusions of the Rowland Suite represent a primitive cumulate end-member of the magmatic system, whereas the varying crystal-poor to crystal-rich Kathleen Ignimbrite eruption sequence represents the evolved and highly fractionated end-member of the system that formed thorough the evacuation of a shared or at least partly linked, compositionally zoned and differentiated source magma chamber or chambers.